DIGITAL LITERACY: THE URGENCY OF DIGITAL SKILL IMPROVEMENT THROUGH E-MODULES - Kuncahyono Kuncahyono; Dian Fitri Nur Aini (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study is to describe the implementation of digital literacy using e-modules and to increase understanding of PGSD students. The type of research used is Classroom Action Research (PTK). The subjects in this study were all PGSD students of Muhammadiyah Malang University, totaling 50 students. Implementation of digital literacy skills using the e-module uses 3 learning stages, namely: (a) software engineering; (b) instructional design; and (c) the level of visual communication. The results of the study show that students' understanding of digital literacy skills includes: 1) The use of SAL-based e-module guidelines can improve student skills in compiling digital teaching materials. 2) The improvement of students' skills in compiling digital teaching materials after using SAL-based e-module guidelines was marked by the increase in student skills in compiling digital teaching materials from 56.8% to 82.5%